Opportunities for developing mountain biking in the Municipality of Bohinj - Katarina Polajnar Horvat; Urška Drofenik (Acta Geographica Slovenica, 2015)
Due to the relatively short travel distances between places, a wide variety of natural and cultural sites in the area, the well-preserved environment, and a large number of forest roads, skid trails, field trails, and hiking trails through the mountains, the Municipality of Bohinj, much of which lies in Slovenia’s largest protected area, Triglav National Park, has great potential for the development of mountain biking. In order to outline the guidelines for effective environmental protection and provide a basis for harmonizing the needs of various users, this article evaluates the prudence of and the need for establishing an appropriate mountain biking management system in the Bohinj Valley, one of the most popular tourism areas in Upper Carniola. A tentative system of trails suitable for this leisure activity is proposed based on an overview of the relevant literature, a survey, and cooperation with various individuals involved with mountain biking. It would also make sense to include these trails in the municipal development plan.